2013
DOI: 10.1017/s1461145713000047
|View full text |Cite
|
Sign up to set email alerts
|

Number of manic episodes is associated with elevated DNA oxidation in bipolar I disorder

Abstract: Bipolar disorder (BD) is a major public health problem characterized by progressive functional impairment. A number of clinical variables have been associated with progression of the disease, most notably number of affective episodes and presence of psychotic symptoms, both of which correlate with greater cognitive impairment, lower response rates for lithium, and possibly lower levels of neurotrophic factors. Oxidative damage to cytosine and guanosine (8-OHdG) has been described as a modulator of DNA methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 66 publications
(92 reference statements)
1
63
1
3
Order By: Relevance
“…It is important to determine the contents of these 2 modified nucleotides and their ratios in order to examine their complete role in psychiatric disorders. Two studies have observed a decreased level of 5-hmC in patients with major DD [87] and bipolar disorder [88]. The results of most of these studies indicate reduced levels of 5-mC and 5-hmC.…”
Section: Epigenetics In Depressionmentioning
confidence: 99%
“…It is important to determine the contents of these 2 modified nucleotides and their ratios in order to examine their complete role in psychiatric disorders. Two studies have observed a decreased level of 5-hmC in patients with major DD [87] and bipolar disorder [88]. The results of most of these studies indicate reduced levels of 5-mC and 5-hmC.…”
Section: Epigenetics In Depressionmentioning
confidence: 99%
“…Several recent studies have reported inconsistent data involving SOD, CAT, GPx, DNA damage and protein carbonylation in bipolar patients (Andreazza et al, 2007b(Andreazza et al, , 2008a(Andreazza et al, , 2009Kapczinski et al, 2011;Soeiro-de-Souza et al, 2013). SOD, GPx and CAT are primary antioxidant enzymes that act against oxidative stress and prevent the oxidation of DNA, protein and lipid (Sabens Liedhegner et al, 2012;Roszkowski, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, free radicals react with guanosine DNA residues and produce 8-hydroxy 2 0 -deoxyguanosine (8-OHdG); free radicals also lead to cytosine damage (Lenaz, 2001;Kohen and Nyska, 2002). Oxidative stress-induced DNA damage in bipolar patients has been reported (Frey et al, 2007;Andreazza, 2012;Soeiro-de-Souza et al, 2013). Furthermore, ROS leads to protein damage measured by protein carbonyl content (PCC).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Scola and collaborators reported that mitochondrial dysfunction may lead to alteration on methylation and hydroxymethylation levels in cortical primary neurons [31]. Oxidative damage to guanosine, measured by 8-hydroxy-2-deoxyguanosine levels (8-OHdG), was found to be higher in patients with BD when compared to healthy controls, and, importantly, it was found to be positively correlated to the number of manic episodes [32]. The same study also found that patients with BD presented decreased global 5-methylcytosine (5mc) levels similarly to the findings reported by Huzayyin and collaborators (2014).…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%